Tripartite interaction among Rufous Hornero, Shiny Cowbirds nestlings, and Philornis torquans complex larvae - Fasano, Agustín Alfonso (2025)
The datasets were used to examine the interaction between an ectoparasitic fly (Philornis torquans complex) and a brood-parasitic bird, the Shiny Cowbird (Molothrus bonariensis), sharing a common host, the Rufous Hornero (Furnarius rufus). The data were collected over seven breeding seasons (2007, 2008, 2009, 2014, 2015, 2023 and 2024) in an 80-ha patch of native forest located in the central region of Santa Fe Province, Argentina. These datasets were used to analyses parasite prevalence, mean abundance, and host selection by the Philornis torquans complex, and their effects on the survival of Rufous Hornero and Shiny Cowbird nestlings.